Characteristics that Affect the Quality of Accounting Information (Study on SIPBOS in the Bandung City Education Office Area) - Hani Fitria Rahmani; Ajeng Andina Mustika Putri Perdana (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the magnitude of the influence of information technology and user competence on the quality of accounting information. The methods used are descriptive and associative methods, using questionnaires. The respondents in this study were treasurer employees and financial staff of the Bandung State High School school who used SIPBOS, the technique used in the sample selection was saturated sampling with a total sample of 54 respondents. The data analysis method is SEM (Structural Equation Modeling) analysis, using the SmartPLS 4.0 program, the results of the study show that information technology does not partially affect the quality of accounting information, while the competence of users has a positive and significant effect on the quality of accounting information.